Body Dimension Factors Affecting Live Weight Estimation Accuracy of Indonesian Local-Thoroughbred Racing Horse - Santie Turangan; Umar Paputungan; Surtijono Edmundus Siswosubroto (Research Journal of Life Science, 2019)
Study was conducted to estimate live weight of Indonesian Local-Thoroughbred racing horse using their chest girth, body length and body volume represented by chest girth and body length dimensions. Data on animal live weight (LW), body length (BL), chest girth (CG) and body volume were collected from male horses (n=188) kept by the owner club members of North Sulawesi Racing Horse. Animal body volume was calculated using cylinder volume formula with CG and BL as component factors of the formula. Data were classified on animal age basis of five groups. Regression analysis was applied for LW with all linear body measurements. Age significantly influenced all body measurements. Simple regression can be recommended to predict live weight of this animal based on body volume with their average age groups as follows: Live weight (Y in kg unit) = - 0.002+1.16 body volume (dm3) with determination coefficient (R2) of 0.98. The multiple regression can also be recommended to estimate accurately live weight of this animal at age average groups as follows: Live weight (Y in kg unit) = - 0.11 - 2.74 chest girth (X1 in cm unit) + 4.92 body length (X2 in cm unit) with R2 of 0.98.